2013
DOI: 10.1021/ja403906d
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study on the Solution-Phase n-Doping of 1,3-Dimethyl-2-aryl-2,3-dihydro-1H-benzoimidazole Derivatives

Abstract: The discovery of air-stable n-dopants for organic semiconductor materials has been hindered by the necessity of high-energy HOMOs and the air sensitivity of compounds that satisfy this requirement. One strategy for circumventing this problem is to utilize stable precursor molecules that form the active doping complex in situ during the doping process or in a postdeposition thermal- or photo-activation step. Some of us have reported on the use of 1H-benzimidazole (DMBI) and benzimidazolium (DMBI-I) salts as sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
266
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(295 citation statements)
references
References 37 publications
18
266
0
Order By: Relevance
“…13,26 Mechanistic studies in the solution phase found that the dopant reacted with the fullerene derivative through hydride or hydrogen atom transfer to afford host radical anions, which were responsible for the doping effect. 27 Comparative studies of the doping efficiency of fullerene-based OSCs with the same dopant in OTFTs also found a significant enhancement in device performance. 28 However, conjugated polymers, as the major class of solution-processable OSCs, are rarely n-doped in devices, especially OTFTs, 14,20,24,29 despite the significant improvement it can have on device parameters, e.g., charge carrier mobility, threshold voltage, channel current on/off ratio and contact resistance.…”
Section: Introductionmentioning
confidence: 94%
“…13,26 Mechanistic studies in the solution phase found that the dopant reacted with the fullerene derivative through hydride or hydrogen atom transfer to afford host radical anions, which were responsible for the doping effect. 27 Comparative studies of the doping efficiency of fullerene-based OSCs with the same dopant in OTFTs also found a significant enhancement in device performance. 28 However, conjugated polymers, as the major class of solution-processable OSCs, are rarely n-doped in devices, especially OTFTs, 14,20,24,29 despite the significant improvement it can have on device parameters, e.g., charge carrier mobility, threshold voltage, channel current on/off ratio and contact resistance.…”
Section: Introductionmentioning
confidence: 94%
“…Through structural optimization they achieve electrical conductivities and thermoelectric power factors as high as 0.5 S.cm −1 and 1.4 μW.m −1 K −2 , respectively. A variety of new organometallic complexes, 87 hydride donors, 1,3-Dimethyl-2-phenyl-2,3-dihydro-1H-benzoimidazole (DMBI), 88 and…”
Section: N-type Organic Thermoelectric Materialsmentioning
confidence: 99%
“…11−16 The doping mechanism occurs by an electron transfer process between the dopant molecule and the host material. 11,17 For p-type doping, the electron is transferred from the host material to the dopant, and for n-type doping the electron transfers from the dopant molecule to the host material. An important difference between doping inorganic semiconductors and doping organic electronic materials is that, for organic doping, the dopant molecules are not bound to their host material by strong covalent bonds.…”
Section: ■ Introductionmentioning
confidence: 99%